Transdermal Insulin Delivery and Microneedles-based Minimally Invasive Delivery Systems - Hong, Yichuan; Yu, Haojie; Wang, Li; Chen, Xiang; Huang, Yudi; Yang, Jian; Ren, Shuning (Current pharmaceutical design, 2022)
Diabetes has become a serious threat to human health, causing death and pain to numerous patients. Transdermal insulin delivery is a substitute for traditional insulin injection to avoid pain from the injection. Transdermal methods include non-invasive and invasive methods. As the non-invasive methods could hardly get through the stratum corneum, minimally invasive devices, especially microneedles, could enhance the transappendageal route in transcutaneous insulin delivery, and could act as connectors between the tissue and outer environment or devices. Microneedle patches have been in quick development in recent years and with different types, materials and functions. In those patches, the smart microneedle patch could perform as a sensor and reactor responding to glucose to regulate the blood level. In the smart microneedles field, the phenylboronic acid system and the glucose oxidase system have been successfully applied on the microneedle platform. Insulin transdermal delivery strategy, microneedles technology and smart microneedles' development would be discussed in this review.